Two steps forward - one step back? Evaluating contradicting child care policies in Germany - Kai-Uwe Müller; Katharina Wrohlich (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
We apply a structural model of mothers' labor supply and child care choices to evaluate the effects of two childcare reforms in Germany that were introduced simultaneously in August 2013. First, a legal claim to subsidized child care became effective for all children aged one year or older. Second, a new benefit called "Betreuungsgeld" came into effect that is granted to families who do not use public or publicly subsidized child care. Both reforms target children of the same age group and are unconditional on the parents' income or employment status, yet affect mothers' incentives for labor supply and child care choices in opposite directions. Our model facilitates estimating the joint reform impact as well as disentangling the individual effects of both policies. A comprehensive data set with information on labor supply, the use of and potential access restrictions to various child care arrangements provides the basis for the empirical analysis. We find the overall effect of both reforms to be small but positive as far as mother's labor supply and the use of formal care is concerned. The legal claim's positive impact on mothers' labor supply and the use of formal child care is largely offset by the negative effect on both outcomes resulting from the introduction of the "Betreuungsgeld".
Keywords: J22; J18; H31; 330; family policy; labor supply; child care; policy evaluation; structural model